Sub-optimal temperatures affect Solanum tuberosum subsp. andigena true potato seed germination - Lapichino, G.=700 1 Incalcaterra, G.
(En, Fr, Es)
ilus., 6 ref.
Keywords: SOLANUM TIBEROSUM; GERMINACION; SEMILLAS; FRIO; COSTA RICA